Salary Survey Report for the Illinois Public Community Colleges, Fall 1989 - Illinois Community Coll. Board, Springfield; Illinois Community Coll. Board, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Drawing from information collected in the annual salary survey conducted by the Illinois Community College Board, this report presents data about compensation received by employees in the 50 Illinois public community colleges. Faculty salary data are based on actual contracts, salaries from faculty salary schedules, part-time faculty salary rates, and overload faculty salary rates. Also included are administrative salaries; other professional salaries; average faculty load information; salaries for positions similar to University Civil Service classifications; salaries of selected administrators; and fiscal year 1989 total salaries actually paid to faculty, administrators, other professionals, and classified staff. Highlighted findings include the following: (1) faculty were paid an average annual salary of $40,757, administrators an average of $42,887, and other professionals an average of $29,618; (2) the average cost of fringe benefits was $2,993 for full-time faculty, $3,346 for administrators, $2,870 for other professionals, and $2,891 for classified staff; (3) fiscal year 1990 weighted average salary increases were 6.7% for faculty, 6.6% for administrators, 6.7% for other professionals, and 7.1% for classified staff; and (4) part-time faculty were paid an average of $311 per credit hour. (JMC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrators; College Faculty; Community Colleges; Contract Salaries; Faculty Workload; Fringe Benefits; Full Time Faculty; Part Time Faculty; Promotion (Occupational); Salaries; School Personnel; State Surveys; Teacher Salaries; Two Year Colleges; Illinois; Numerical/Quantitative Data; Reports, Research